(untitled) (Research, Society and Development, 2022)
The coffee production chain has great socio-economic importance in Brazil, generating foreign exchange with great job-generating capacity. The Brazilian coffee production is circa 2.863 k tons and coffee research has contributed to the development of new technologies in order to increase yield. However, the size of plots used for coffee experiments has been variable and mostly based on the empirical researcher’s experience. Therefore, this research was carried out aiming to determine the optimal size of experimental plots to evaluate field growing parameters of Arabica coffee. The modified maximum curvature model and the comparison of variances were the methods used. It is concluded that 2, 3, 3, and 6 plants per useful experimental plot of Arabica coffee are enough to evaluate the field growing parameters plant height, plant canopy diameter, vigor, and wet mass, respectively by the method of modified maximum curvature. Two plants per experimental plot were required when using the variance comparison method to the parameters plant height, and plant canopy diameter, and 4 plants were enough to the parameters vigor and wet mass. In general, four useful plants per experimental plot were enough using the variance comparison method and six useful plants when using the modified maximum curvature method.